Evaluation of the intention to use the electronic medical record (EMR) by health professionals in healthcare facilities of Libreville and Owendo in Gabon. Issue 4 (22nd November 2022) - Moukoumbi Lipenguet, Gaëtan; Ngoungou, Edgard-Brice; Roberts, Tamara; Ibinga, Euloge; Amani Gnamien, Prudence; Engohang-Ndong, Jean; Wittwer, Jérôme
Abstract: Introduction: Health systems in several countries have integrated information and communication technologies into their operations. Electronic medical records (EMRs) are at the core of patient care. The working of these EMRs requires their acceptance and use by medical and paramedical personnel. The objective of this study was to empirically evaluate the intention of health professionals to use these EMRs. Materials and Methods: A questionnaire on the intention of health professionals to use the EMR was developed following a Likert scale. The survey was done via in-person interviews of health professionals in major health facilities in the cities of Libreville and Owendo in Gabon. The technology acceptance model (TAM) was tested using a step-down logistic regression analysis to identify the main factors explaining the intention of health professionals to use the EMR. Results: A total of 218 health professionals responded to the questionnaire. Thirty-eight percent (38%) of respondents were male. The average age was 41.33 years (±8.98 years) and the average length of service at work in the system was 12.02 years (±8.47 years). The integrated model showed that the intention to use the EMR was significantly associated with the perceived usefulness, the subjective standard, and experience. No socio-demographic variables explained the intention to use the EMR. Conclusion: The perceived ease, familiarity with the computer, and motivation are not associated with the intention to use the EMR. Actions should be taken to raise awareness and train health professionals to motivate them to accept and use EMRs in their medical practices. Lay Summary: Health systems in several countries have opted to implement electronic health records (EMRs) to track patients throughout their care. The objective behind these EMRs is to allow for the exchange of patient information between physicians and/or between care facilities for continuity of care. The operation of this system requires that it be accepted by the health care staff who are the primary users. This study assesses the intention of health professionals to use the EMR in the management of the Gabonese patient. A questionnaire was administered to health professionals to measure their intention to use the EMR. Intention to use the EMR was based on perceived usefulness of the EMR, subjective norm (influence of colleagues), and experience with the use of IT devices in patient care. However, we regret the lack of staff training in the use of computers in medical practice. This is a real obstacle to the use of EMRs in healthcare facilities.